A Comparison Study of the Effects of Romantic Films and Fictional Stories on Romantic Beliefs among Young Adults - Aura Ratu Aulia; Griselda Callista; Hasya Ashila Supriatna; Muhammad Ihsan Fadhilah; Syifa Hana Nabila; Zaira Yasmina Faizal (unprimdn.ac.id, 2025)
This study aims to explore the role of media, specifically romantic films and fictional stories, in shaping romantic beliefs among early adults. An experimental method was employed with a pre-test and post-test design across two groups. A total of 50 participants (aged 20–30) were divided into two groups: the first group (n=25) watched romantic films, while the second group (n=25) read romantic fiction. Changes in romantic beliefs were measured using a Likert scale ranging from 1 to 7. The results indicated that the average romantic beliefs score of the film group increased from 3.2 to 4.1 (p < 0.01), while the fiction group showed an increase from 3.3 to 3.8 (p < 0.05). Statistical analysis using an independent t-test revealed that the score increase in the film group was significantly greater than in the fiction group (t(58) = 2.89, p < 0.01). These findings suggest that visual narratives in films are more effective at eliciting emotions and reinforcing beliefs about romantic relationships compared to written text. These results also have practical implications that film media can be used as a psychological and educational intervention approach related to romantic relationships in early adulthood.